(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To determine the prevalence of malnutrition and analyze factors associated with nutritional status in post-gastrectomy patients with gastric cancer at Nghe An Oncology Hospital in 2025. Methods: A cross-sectional descriptive study was conducted on 120 patients who underwent gastric cancer surgery at Nghe An Oncology Hospital from January 2025 to September 2025. Results: The postoperative malnutrition rate according to the PG-SGA scale was 53.3%, of which severe malnutrition accounted for 21.6%. The malnutrition rates based on BMI and Albumin were 52.5% and 38.3%, respectively. There was a significant association between the nutritional status of postoperative gastric cancer patients and factors including surgical indications, postoperative fever, unintentional weight loss within one month, loss of subcutaneous fat, muscle wasting, and edema (p < 0.05). Conclusion: Comprehensive nutritional assessment and evaluation of associated factors should be performed for postoperative gastric cancer patients to enable timely and appropriate nutritional interventions, thereby improving treatment response and efficacy.